Pengaruh Penerapan Digital Marketing, Kemudahan Digital Payment, dan Manajemen Keuangan terhadap Kinerja Keuangan UMKM di Kemiling Kota Bandar Lampung - Rif'atul Muna; Eksa Ridwansyah; Destia Pentiana; Damayanti Damayanti (Jurnal Riset Akuntansi Soedirman, 2025)
This study aims to analyze the influence of digital marketing implementation, ease of digital payment, and financial management on the financial performance of MSMEs in Kemiling, Bandar Lampung. Using a quantitative approach, primary data were collected through questionnaires from 120 MSME respondents selected via purposive sampling. Data were analyzed using multiple linear regression with SPSS version 25. The results indicate that while digital marketing has a negative and non-significant effect, both digital payment and financial management significantly and positively influence MSME financial performance. Simultaneously, all three variables contribute to enhancing the competitiveness and sustainability of MSMEs in the digital era. This study underscores the importance of optimizing digital technology adoption balanced with prudent financial management to improve MSME financial outcomes.